2021
DOI: 10.3390/ijms22158080
|View full text |Cite
|
Sign up to set email alerts
|

Coming from the Wild: Multidrug Resistant Opportunistic Pathogens Presenting a Primary, Not Human-Linked, Environmental Habitat

Abstract: The use and misuse of antibiotics have made antibiotic-resistant bacteria widespread nowadays, constituting one of the most relevant challenges for human health at present. Among these bacteria, opportunistic pathogens with an environmental, non-clinical, primary habitat stand as an increasing matter of concern at hospitals. These organisms usually present low susceptibility to antibiotics currently used for therapy. They are also proficient in acquiring increased resistance levels, a situation that limits the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 449 publications
(517 reference statements)
0
26
0
Order By: Relevance
“… Pseudomonas aeruginosa is a nosocomial opportunistic pathogen ( 1 , 2 ), producing infections in immunocompromised patients and in people with underlying diseases ( 3 8 ). This bacterium is able to grow in several body locations, being one of the main causative agents of chronic infections in the lungs of cystic fibrosis (CF) or chronic obstructive pulmonary disease (COPD) patients ( 3 ) and also being a major cause of urinary tract infections (UTIs) ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“… Pseudomonas aeruginosa is a nosocomial opportunistic pathogen ( 1 , 2 ), producing infections in immunocompromised patients and in people with underlying diseases ( 3 8 ). This bacterium is able to grow in several body locations, being one of the main causative agents of chronic infections in the lungs of cystic fibrosis (CF) or chronic obstructive pulmonary disease (COPD) patients ( 3 ) and also being a major cause of urinary tract infections (UTIs) ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…received particular attention due to its ability to cause urinary tract infection, bacteremia, and infective endocarditis [ 8 , 9 ]. Enterococci are Gram-positive, opportunistic microorganisms that normally inhabit the human gastrointestinal tract [ 10 ]. Among Enterococcus spp., E. faecium and E. faecalis are the third leading cause of nosocomial infections after S. aureus and P. aeruginosa [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…136 Overall, the majority of enteric bacteria and viruses reported in the studies targeted and detected commensal enteric microbiota or opportunistic pathogens that typically only cause disease in immunocompromised individuals. Recent evidence reveals the growing relevance of opportunistic pathogens in clinical settings, particularly in the context of their low susceptibility to antibiotics and environmental origins 137 . Frank pathogens, which cause disease even in immunocompetent individuals are less represented in the review, making up less than half (39%) of all unique microbes reported at the strain and species levels across all studies (Table 2).…”
Section: Discussionmentioning
confidence: 99%